An association analysis between PRL genotype and milk production traits in Italian Mediterranean river buffalo. Issue 4 (20th November 2017) - Li, Jun; Liang, Aixin; Li, Zipeng; Du, Chao; Hua, Guohua; Salzano, Angela; Campanile, Giuseppe; Gasparrini, Bianca; Yang, LiGuo
Abstract : This Research Communication describes the association between genetic variation within the prolactin ( PRL ) gene and the milk production traits of Italian Mediterranean river buffalo ( Bufala mediterranea Italiana). High resolution melting (HRM) techniques were developed for genotyping 465 buffaloes. The association of genetic polymorphism with milk production traits was performed and subsequently the effects of parity and calving season were evaluated. Single nucleotide polymorphisms (SNPs) were identified at exons 2 and 5 and at introns 1 and 2. All the SNPs were in Hardy–Weinberg equilibrium, and statistical analysis showed that the polymorphism of intron1 was significantly ( P < 0·05) associated with milk yield, milk protein content and peak milk yield. The average contribution of the intron1 genotype ( r 2 intron1 ) to total phenotypic variance in milk production traits was 0·09, and the TT genotype showed lower values than CC and CT genotypes. A nonsynonymous SNP was identified in exon 2, which resulted in an amino acid change from arginine to cysteine. Moreover, the polymorphism of exon 2 was associated significantly with milk fat content ( P < 0·05), and the buffaloes with TT genotype showed higher total fat content than the buffaloes with CT genotype. These findings provide evidence that polymorphisms of the buffalo PRL gene are associated with milk production traits and PRL can be used as a candidate gene for marker-assisted selection in Italian Mediterranean river buffalo breeding.